HR-MS Based Untargeted Lipidomics Reveals Characteristic Lipid Signatures of Wilson’s Disease - Zhi, Yixiao; Sun, Yujiao; Jiao, Yonggeng; Pan, Chen; Wu, Zeming; Liu, Chang; Su, Jie; Zhou, Jie; Shang, Dong; Niu, Junqi; Hua, Rui; Yin, Peiyuan (Frontiers in Pharmacology, 2021)
Background & Aims: The diagnosis of Wilson disease (WD) is still challenging by clinical or genetic criteria. A typical early pathological change of WD is the increased liver lipids deposition and lowered serum triglyceride (TG). Therefore, the contents of serum lipids may provide evidence for the screen of biomarkers for WD. Methods: 34 WD patients, 31 WD relatives, and 65 normal controls were enrolled in this study. Serum lipidomics data was acquired by an ultra-high-performance liquid chromatography high-resolution mass spectrometry system, and the data were analyzed by multivariate statistical methods. Results: Of all 510 identified lipids, there are 297 differential lipids between the WD and controls, 378 differential lipids between the relatives and controls, and 119 differential lipids between the patients and relatives. In WD, the abundances of most saturated TG were increased, whereas other unsaturated lipids decreased, including phosphatidylcholine (PC), sphingomyelin (SM), lysophosphatidylcholine (LPC), ceramide (Cer), and phosphatidylserine (PS). The correlation networks were built among the different groups and the potential mechanisms of the differential lipids were discussed. Interestingly, similar lipids features of WD are also found in their relatives, which indicated the changes may also be related to the mutation of the ATP7B gene. We also found many serum lipid species may be used as biomarkers for WD. The areas under the receiver operating characteristic curve (AUC) of PS (35:0), PS (38:5), and PS (34:0) were 0.919, 0.849, and 0.907. The AUCs of TG (38:0) and CerG1(d42:2) were 0.948 and 0.915 and the AUCs of LPC (17:0) and LPC (15:0) were 0.980 and 0.960, respectively. These lipids exhibit good diagnostic performance for WD. Conclusions: Lipid deregulation is another important hallmark of WD besides the deposition of copper. Our lipidomic results provide new insights into the diagnostic and therapeutic targets of WD.